ADAPTIVE GOVERNANCE IN PARATRANSIT FORMALIZATION: INTEGRATING RIDE-HAILING AND URBAN MINIBUSES IN BOGOR - Wilianus Chandra Wijaya; Sri Roekminiati; Dendy Patrija W (International Journal of Multidisciplinary Reseach, 2026)
This study examines the policy dynamics of paratransit transportation formalization in Bogor City through an Adaptive governance perspective, focusing on the implementation of Mayor Regulation Number 45 of 2023, which integrates ride-hailing (ojek online) and urban minibuses (angkutan kota) into the formal public transportation system. The research aims to analyze the local government's adaptive regulatory capacity, collaborative multi-actor governance mechanisms, and the dynamics of negotiation and bureaucratic learning in managing the transition from an informal to an integrated transportation system. A qualitative approach with an explanatory case study design and process tracing technique was employed, involving six key informants through semi-structured interviews, regulatory document analysis, and field observation. The findings reveal that Bogor City's adaptive regulatory capacity is at a developing stage, with uneven implementation outcomes: ride-hailing driver certification reached 68.2%, angkot-to-BRT feeder conversion 44.2%, and digital payment integration 37.5% of set targets. Multi-actor collaboration mechanisms have been established and produced substantive policy compromises, yet the resulting legitimacy remains partial. The study concludes that Bogor City exhibits a governance in transition profile that requires strengthened institutional capacity, standardized monitoring-evaluation systems, and more carefully calibrated incentive mechanisms for all stakeholders.